2016
DOI: 10.1590/1678-775720160032
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antimicrobial susceptibility of enteric rods and pseudomonads isolated from the dental prostheses biofilm

Abstract: Aspiration of oral bacteria leads to cardiac and respiratory infectious diseases and dentures can act as a reservoir for pathogenic microorganisms.Objective:To determine the occurrence and the in vitro antimicrobial susceptibility of enteric rods and pseudomonads from the denture biofilm of 52 subjects at the Center for Dental Specialties of Sobral/ Ceara, Brazil.Material and Methods:Denture biofilm was collected and samples plated on MacConkey agar. The isolated bacterial colonies were identified using the BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
0
11
0
7
Order By: Relevance
“…In this study, we tested three bacterial strains: Escherichia coli , Klebsiella pneumonia , and Streptococcus mutans . Previous studies performed on denture bases typically made of heat-curing polymethyl methacrylate have shown that the most colonized microorganisms on acrylic bases are Klebsiella pneumonia and Escherichia coli [ 22 ]. In the population of denture users, bad breath is due to the metabolic reactions of the proliferation of Gram-negative bacteria, including the Enterobacteriaceae family [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested three bacterial strains: Escherichia coli , Klebsiella pneumonia , and Streptococcus mutans . Previous studies performed on denture bases typically made of heat-curing polymethyl methacrylate have shown that the most colonized microorganisms on acrylic bases are Klebsiella pneumonia and Escherichia coli [ 22 ]. In the population of denture users, bad breath is due to the metabolic reactions of the proliferation of Gram-negative bacteria, including the Enterobacteriaceae family [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unusual oral cavity microorganisms have been previously isolated from dentures and were reported by other researchers. [ 33 34 35 36 37 ] Umeda et al . reported Helicobacter pylori in the oral cavity of a patient with periodontal pockets that existed even after extirpation of the bacterium from the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…All organisms were susceptible to ciprofloxacin, and most species were resistant to amoxicillin and amoxicillin-clavulanate. Therefore, preventive programs for biofilm control are essential in avoiding colonization of dental prostheses and its resulting multidrug-resistant bacterial infections [ 21 ].…”
Section: Reviewmentioning
confidence: 99%